Trends in infrastucture regulation and financing : international experience and case studies from Germany - Hirschhausen, Christian-von.; Beckers, Thorsten; Mitusch, Kay. (Cheltenham, UK ; Northampton, MA : Edward Elgar Pub., 2004)
This is a balanced representation of international trends in infrastructure regulation and financing. Based on recent developments in microeconomic theory, it comprehensively discusses the role of the state and the private sector in infrastructure provision.
Includes bibliographical references and index.
osa 26/09/2016
Loans
Keywords: Infrastructure (Economics) -- Government policy -- Case studies; Infrastructure (Economics) -- Finance -- Case studies; Germany